Virtual milgram: empathic concern or personal distress? Evidence from functional MRI and dispositional measures - Cheetham, Marcus; Pedroni, Andreas; Antley, Angus; Slater, Mel; Jäncke, Lutz (Frontiers in Human Neuroscience, 2009)
One motive for behaving as the agent of another’s aggression appears to be anchored in as yet unelucidated mechanisms of obedience to authority. In a recent partial replication of Milgram’s obedience paradigm within an immersive virtual environment, participants administered pain to a female virtual human and observed her suffering. Whether the participants’ response to the latter was more akin to other-oriented empathic concern for her well-being or to a self-oriented aversive state of personal distress in response to her distress is unclear. Using the stimuli from the previous study, this event-related fMRI-based study analysed brain activity during observation of the victim in pain compared with no pain. This contrast revealed activation in pre-defined brain areas known to be involved in affective processing, but not those commonly associated with affect sharing (e.g. ACC and insula). We then examined whether different dimensions of dispositional empathy predict activity within the same pre-defined brain regions: While personal distress and fantasy (i.e. tendency to transpose oneself in fictional situations and characters) predicted brain activity, empathic concern and perspective taking predicted no change in neuronal response associated with pain observation. These exploratory findings suggest that there is a distinct pattern of brain activity associated with observing the pain-related behaviour of the victim within the context of this social dilemma, that this observation evoked a self-oriented aversive state of personal distress, that the objective ‘reality’ of pain is of secondary importance for this response. These findings provide a starting point for an experimentally more rigorous approach to the investigation of obedience.